2020
DOI: 10.18203/2349-3291.ijcp20204959
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical profile and associated risk factors for congenital malformations in neonates: a hospital based prospective study

Abstract: Background: Congenital malformations are major cause of neonatal morbidity and mortality and account for 8-10% of all peri-natal deaths especially in developing countries. Incidence of congenital malformation is increasing owing to reduction in other causes of neonatal deaths due to improvement in perinatal care worldwide. This study was aimed to evaluate the incidence, perinatal variables and contributing risk factors associated with birth defects that will help to plan future strategies for prevention, early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…In this study Males are more affected than females (61.3%) versus (38.7% ) in every type of GIT anomaly in this study .The male preponderance are similar to several studies where congenital anomalies in general including GIT is more common in males than females [6,12,17,[18][19][20].The explanation may be due to the fact that autosomal recessive disorders are more common in males.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study Males are more affected than females (61.3%) versus (38.7% ) in every type of GIT anomaly in this study .The male preponderance are similar to several studies where congenital anomalies in general including GIT is more common in males than females [6,12,17,[18][19][20].The explanation may be due to the fact that autosomal recessive disorders are more common in males.…”
Section: Discussionsupporting
confidence: 86%
“…The explanation for this finding is that affected premature neonates may have not survived to reach the tertiary hospital. Opposite to this a surprising finding in study at India found that majority of malformed neonates were pretem in 76.1% of cases with 68 % of malformed babies had birth weight <2.5 kg [17].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation